SOSIALISASI AGRO-ENTREPRENEURSHIP BAGI KELOMPOK TANI MENGANI MENUJU PERTANIAN RAMAH LINGKUNGAN DI KINTAMANI-BALI - Pande Komang Suparyana; Putu Eka Pasmidi Ariati; I Ketut Widnyana; Muhammad Nursan; Dudi Septiadi; Aeko Fria Utama FR; I G N Anom (Denpasar Institute, 2019)
Mengani village which is located on a hill, makes agricultural land has the potential to develop environmentally friendly agriculture because it is close to a water source and there is almost no contamination on the land. The use of organic fertilizer has begun to be applied by farmers, but the use of pesticides still applies chemical pesticides. The impact of chemical pesticides is not only harmful to plants and the environment, but can cause new types of pests and diseases to attack plants. Organic pesticides are not used by farmers in Mengani Village due to farmers' lack of understanding of the application of effective and efficient use of organic pesticides. So the Farmers' Group needs to get management socialization in Agro-Entrepreneurship towards environmentally friendly and sustainable agriculture. This activity provides knowledge and skills for farmers. After conducting training and counseling, farmers can already know the pests that attack the agricultural land and control techniques. Farmers can also do post-harvest handling that provides higher economic value than before training. In general, farmers who participated in the training showed a good and active response during this activity. At the end of training and counseling, the farmer knows the costs and marketing efficiency of the Cabbage commodity on his farm